2017
DOI: 10.1038/s41598-017-03560-9
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tagging of Mediterranean fin whales: working towards the identification of critical habitats and the focussing of mitigation measures

Abstract: Mediterranean fin whales comprise a genetically distinct population, listed as Vulnerable (VU) in the IUCN Red List. Collisions with vessels are believed to represent the main cause of human-induced mortality. The identification of critical habitats (including migration routes) incorporating satellite telemetry data is therefore crucial to develop focussed conservation efforts. Between 2012 and 2015 thirteen fin whales were equipped with satellite transmitters, 8 in the Pelagos Sanctuary (although two ceased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 80 publications
(91 reference statements)
0
67
0
Order By: Relevance
“…Studies should include oceanographic and biological information, such as prey field density and frontal systems, in their spatial analyses to expand our current understanding of mobulid movement patterns (e.g., Papastamatiou et al, 2012;McCauley et al, 2014). Together, these data can be used in ecosystem niche modeling to identify potential new regions of importance to mobulid species (Panigada et al, 2017). The position uncertainty inherent in light-based geolocation tags impedes the incorporation and comparison of oceanographic data with movements as prey fields and oceanographic features can vary widely within the error radius of a single position estimate.…”
Section: Critical Habitatsmentioning
confidence: 99%
“…Studies should include oceanographic and biological information, such as prey field density and frontal systems, in their spatial analyses to expand our current understanding of mobulid movement patterns (e.g., Papastamatiou et al, 2012;McCauley et al, 2014). Together, these data can be used in ecosystem niche modeling to identify potential new regions of importance to mobulid species (Panigada et al, 2017). The position uncertainty inherent in light-based geolocation tags impedes the incorporation and comparison of oceanographic data with movements as prey fields and oceanographic features can vary widely within the error radius of a single position estimate.…”
Section: Critical Habitatsmentioning
confidence: 99%
“…Previous studies reported the presence of the species in the study area since the beginning of the 1990s, with an increased occurrence after 20 years (Arcangeli et al, ; Arcangeli et al, ). It was recently suggested that the central Tyrrhenian Sea is an opportunistic feeding ground while transiting to the Ligurian Sea in summer (Arcangeli et al, ; Panigada et al, ; Santoro et al, ), with a marked change in the use of the area from the early 1990s, when it was primarily considered as a transit zone (Marini et al, ; Nascetti & Notarbartolo di Sciara, ). More fin whales have been observed spending longer periods in the central Tyrrhenian Sea for feeding purposes instead of just moving through this area, possibly due to the presence of two gyres (Barale, Jaquet, & Ndiaye, ; Vetrano, Napolitano, Iacono, Schroeder, & Gasparini, ), which enhance the productivity in the region.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, distance from the nearest coast was the environmental variable with the greatest explanatory power for fin whales, with a preference for relatively greater distances from the coast in the north and shorter in the south (Pontine Archipelago) with a depth range of 200-1,000 m and some topographic complexity (top of seamounts). Fin whales in the Mediterranean are most common in deep waters (400-2,500 m), but they can occur in slope and shelf waters as well, depending on the distribution of their prey (Gannier, Drouot, & Goold, 2002;Laran & Gannier, 2008; Notarbartolo di Sciara, Zanardelli, Jahoda, Panigada, & Airoldi, 2003;Pace, Miragliuolo, & Mussi, 2012;Panigada, Notarbartolo di Sciara, & Zanardelli, 2006;Panigada et al, 2017). Fin whale summer distribution and its interannual variability are closely linked to spatial and temporal interactions with zooplankton concentrations, demonstrating large-scale fidelity corresponding to the prey spatial and temporal predictable distribution, and mesoscale fidelity with higher density in the areas where northern krill (Meganyctiphanes norvegica) tend to concentrate (Cotté, Guinet, Taupier-Letage, Mate, & Petiau, 2009;Littaye, Gannier, Laran, & Wilson, 2004).…”
Section: Fin Whalesmentioning
confidence: 99%
“…To date, there are no studies using satellite telemetry data to reveal long-range movements of Bryde's whales. Tags with short prongs, such as LIMPET tags should be used as Bryde's have a thin blubber layer (see use on fin whales (Balaenoptera physalus) Panigada et al, 2017). Satellite telemetry studies would be particularly effective in oceanic regions where there are inshore and offshore whale populations [e.g., South Africa (Best, 2001)], but also where there are small, but genetically diverse populations [e.g., Hauraki Gulf, New Zealand (Tezanos-Pinto et al, 2017)] to determine connectivity.…”
Section: Movementmentioning
confidence: 99%